Normal Rate of Speech in Kannada - CS, Venkatesh; G, Purushothama; MS, Poornima (Journal of All India Institute of Speech and Hearing)
Traditionally ’Rate of Speech’ is defind as the number of words spoken per minute during a speech performance. That would include all pauses — intentional and unintentional and meaningful words spoken in unit elapsed time. In this study, the number of syllables per minute were onsidered instead of words.